2020
DOI: 10.1002/anie.202004449
|View full text |Cite
|
Sign up to set email alerts
|

Sterically Shielded Heptamethine Cyanine Dyes for Bioconjugation and High Performance Near‐Infrared Fluorescence Imaging

Abstract: The near-infrared window of fluorescent heptamethine cyanine dyes greatly facilitates biological imaging because there is deep penetration of the light and negligible background fluorescence.H owever,d ye instability,a ggregation, and poor pharmacokinetics are current drawbacks that limit performance and the scope of possible applications.A ll these limitations are simultaneously overcome with an ew molecular design strategy that produces acharge balanced and sterically shielded fluorochrome.T he key design fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
126
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 70 publications
6
126
0
Order By: Relevance
“…We found that Pttc‐SeBTa‐NIR1270 Pdots were optically unstable in aqueous solutions especially under light excitation while the Pttc‐SeBTa‐NIR1270 polymers were very stable in most organic solvents. This phenomenon is very similar to indocyanine green [16] with resembling chemical construction in which the mechanisms of the regioselective cleavage on the heptamethine cyanines by exogenously generated 1 O 2 have been claimed experimentally and computationally [3a, 17] . On the other hand, NIR1125 and NIR1380 analogues exhibited high stability in organic solvents and in Pdot forms.…”
Section: Resultssupporting
confidence: 70%
“…We found that Pttc‐SeBTa‐NIR1270 Pdots were optically unstable in aqueous solutions especially under light excitation while the Pttc‐SeBTa‐NIR1270 polymers were very stable in most organic solvents. This phenomenon is very similar to indocyanine green [16] with resembling chemical construction in which the mechanisms of the regioselective cleavage on the heptamethine cyanines by exogenously generated 1 O 2 have been claimed experimentally and computationally [3a, 17] . On the other hand, NIR1125 and NIR1380 analogues exhibited high stability in organic solvents and in Pdot forms.…”
Section: Resultssupporting
confidence: 70%
“…Incorporation of bulky groups can provide direct steric hindrance to -stacking, which inhibits H-aggregation. This approach was particularly used in solutions, [125,126] solid state [127] and in dye-loaded polymeric materials. [128] It is also attractive for dye-loaded NEs, because incorporation of bulky lipophilic groups can both improve oil solubility and decrease the ACQ.…”
Section: Brightness Of Dye-loaded Nesmentioning
confidence: 99%
“…[13] But an inherent problem with deep-red and near-infrared fluorophores is the large hydrophobic surface areas of the p-extended molecules which can overwhelm the targeting and pharmacokinetic properties of the attached peptide (Scheme 1). [14,15] At present, the standard solution is to simply decorate the fluorophore structure with multiple charged functional groups [16] but this approach can be problematic because ahighly charged fluorescent label can alter as mall peptidestargeting properties. [17] Here we describe ac onceptually new way to create ad eep-red fluorescent peptide for high-performance bioimaging.The key design element is aself-threaded molecular Figure-eight architecture with ab uried fluorophore.T he literature contains asmall scattered collection of publications describing Figure-eight molecules, [18][19][20][21][22][23][24] and afew of them are self-threaded structures, [25][26][27] although none of the latter incorporate peptides or were designed for ap ractical application such as fluorescence imaging.T he buried fluorophore is as quaraine dye that exhibits narrow and intense deep-red absorption and emission bands (ex:6 40-660 nm, em:6 60-680 nm).…”
Section: Introductionmentioning
confidence: 99%